Research on using Aquilaria sinensis callus to evaluate the agarwood-inducing potential of fungi. - Zhikai Wang; Guoying Zhou; Jungang Chen; Xinyu Miao; Yandong Xia; Zhuang Du; Junang Liu (PLoS ONE)
Agarwood is a precious resinous heartwood highly valued for its cultural, religious, and medicinal significance. With the increasing market demand, natural agarwood resources are rapidly depleting, making the development of effective artificial induction methods for agarwood highly significant. This study aims to explore the feasibility of using callus tissue to assess the ability of fungi to induce agarwood formation. We selected two fungi isolated from Aquilaria sinensis, W-1 (Podospora setosa) and W-15 (Alternaria alstroemeriae), and used the known agarwood-inducing fungi YMY (Pestalotiopsis sp.) as a positive control, by treating A. sinensis callus with their fermented filtrates. The experimental results showed that W-1 and W-15 treatments significantly enhanced the activity of Superoxide dismutase (SOD) and Peroxidase (POD) in the callus tissue and upregulated the expression of 3-hydroxy-3-methylglutaryl-CoA synthase (HMGS), 1-deoxy-D-xylulose-5-phosphate reductoisomerase (DXR), and sesquiterpene synthase (ASS-1). GC-MS analysis further confirmed that the contents of sesquiterpenes and aromatic compounds in A. sinensis treated with W-1 and W-15 were significantly elevated, suggesting that these fungi possess the capacity to induce the formation of agarwood. This study demonstrates that using callus tissue to screen fungi capable of inducing agarwood is feasible and effective, providing new insights for screening fungi resources that efficiently induce agarwood formation in the future.